Design and implementation of a nonlinear robust controller based on the disturbance observer for the active spray boom suspension - Cui, Longfei; Xue, Xinyu; Kong, Wei; Ding, Suming; Gu, Wei; Le, Feixiang (International Journal of Agricultural and Biological Engineering, 2023)
Spray boom vibrations are one of the main causes of the uneven distribution of agrochemicals. Using active suspension to maintain the correct height of nozzles is critical for obtaining a uniform spray pattern and minimizing the possibility of spray drift. However, the electro-hydraulic active pendulum boom suspension has nonlinear uncertain factors such as parameter uncertainties, external disturbances, model error, etc., which complicate the design of the controller. Therefore, this paper proposes a nonlinear robust feedback control method with disturbances compensation, which integrates a robust controller and disturbance observers through the backstepping method. Initially, to verify the performance of the controller, the Lyapunov stability theory is used to prove that the proposed controller can guarantee the given transient performance and the final tracking accuracy. Furthermore, taking the active suspension of a 28 m wide boom driven by a single-rod hydraulic actuator as an implementation case, the proposed NRCDC controller was compared with a variety of control schemes through a rapid control prototype of a pendulum active suspension. Finally, the proposed control scheme is implemented on a self-propelled sprayer with a boom of 12 m in length. The field test results show that all the performance indicators of the NRCDC controller are better than the other three conventional controllers. Both laboratory and field tests have verified the effectiveness and high performance of the proposed controller. Keywords: robust control, sprayer boom, boom suspension, hydraulic control system, disturbance observer DOI: 10.25165/j.ijabe.20231601.7007 Citation: Cui L F, Xue X Y, Kong W, Ding S M, Gu W, Le F X. Design and implementation of a nonlinear robust controller based on the disturbance observer for the active spray boom suspension. Int J Agric & Biol Eng, 2023; 16(1): 153–161.